Risk, risk factors, and screening of malignancies in dermatomyositis: current status and future perspectives - Liu, Shubei; Zhang, Zhihong; Yan, Shushan; Yang, Chunjuan; Wang, Bin; Shen, Minning; Wang, Zhenhua; Xu, Donghua (Frontiers in Oncology, 2025)
Dermatomyositis (DM) is an idiopathic inflammatory myopathy with characteristic cutaneous inflammation and heterogeneous systemic involvements, and is strongly associated with risk of malignancy. This review summarizes the incidence of malignancies, risk factors associated with malignancies, and cancer screening methods in DM patients. Large population-based cohort studies and meta-analyses have provided strong evidence for the significantly elevated incidence of malignancies in DM patients. Common malignancies occurring in DM patients mainly include ovarian cancer, lung cancer, breast cancer, pancreatic cancer, stomach cancer, hematologic malignancies, and colorectal cancer. Clinicians should cautiously consider the risk of malignancy in DM patients during diagnosis and treatment, conducting regular screening and monitoring to facilitate early detection and treatment of malignancies. Among myositis-specific antibodies, anti-transcription intermediary factor 1γ antibodies are strongly linked to malignancy risk. Other factors such as older age, male gender, dysphagia, skin necrosis, cutaneous vasculitis, rapid onset of the disease, elevated creatinine kinase, and elevated C-reactive protein are closely associated with the risk of malignancy. DM patients with these features need receive screening for malignant tumors or close monitoring and follow-up. DM patients, especially those within 3 years of onset, have a high risk of cancer and should receive careful cancer screening according to their risk stratification. Conventional screening tools such as imaging examinations and tumor marker tests are not effective in detecting malignancies among DM patients. Current cancer screening workflows available for DM patients largely mirror those used in the general population but may not fully address DM-specific characteristics, and the best strategy for screening cancer in DM patients is still lacking. To facilitate earlier detection and diagnosis of DM-associated cancer and thereby improve outcomes, more effective cancer detection tools and personalized malignancy screening workflows specifically tailored to the features of DM and their individual risk stratification are warranted.